Temperate Zone Plant Natural Products-A Novel Resource for Activity against Tropical Parasitic Diseases - Hameed, Hamza; King, Elizabeth F B; Doleckova, Katerina; Bartholomew, Barbara; Hollinshead, Jackie; Mbye, Haddijatou; Ullah, Imran; Walker, Karen; Van Veelen, Maria; Abou-Akkada, Somaia Saif; Nash, Robert J; Horrocks, Paul D; et al. (Pharmaceuticals (Basel, Switzerland), 2021)
The use of plant-derived natural products for the treatment of tropical parasitic diseases often has ethnopharmacological origins. As such, plants grown in temperate regions remain largely untested for novel anti-parasitic activities. We describe here a screen of the PhytoQuest Phytopure library, a novel source comprising over 600 purified compounds from temperate zone plants, against in vitro culture systems for Plasmodium falciparum, Leishmania mexicana, Trypanosoma evansi and T. brucei. Initial screen revealed 6, 65, 15 and 18 compounds, respectively, that decreased each parasite's growth by at least 50% at 1-2 µM concentration. These initial hits were validated in concentration-response assays against the parasite and the human HepG2 cell line, identifying hits with EC50 < 1 μM and a selectivity index of >10. Two sesquiterpene glycosides were identified against P. falciparum, four sterols against L. mexicana, and five compounds of various scaffolds against T. brucei and T. evansi. An L. mexicana resistant line was generated for the sterol 700022, which was found to have cross-resistance to the anti-leishmanial drug miltefosine as well as to the other leishmanicidal sterols. This study highlights the potential of a temperate plant secondary metabolites as a novel source of natural products against tropical parasitic diseases.
Keywords: malaria; drug discovery; natural products; Surra; leishmaniasis; temperate zone; African trypanosomiasis; neglected tropical diseases